Clinical Significance of Elevated Serum IL-36γ Levels in Patients with Early-Stage Hashimoto’s Thyroiditis - Saba Arif, Azra Sakhawat, Naveeda Nawaz, Maria Sarfraz, Rabbia Shabbir, Saira Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypothyroidism was the diagnosed and treated as a result of health related quality of life issues. The aim of this study was that to evaluate the effect of IL-36 γ, Tg-Ab and TOP-Ab in the Hashimoto’s Thyroiditis (HT). Study design: This was a cross sectional study conducted at Rawal Institute of health sciences, Islamabad duration of study was six month, from April 2022 to September 2022. Methods: A total number of the patients was n=150 which divided into two group, control and HT group. To perform EISA for the estimation of free triiodothyronine 3, 4 (FT3, FT4), thyroid stimulating hormone (TSH), thyroid peroxidase antibody (TOP-Ab) and thyroid globulin antibody (Tg-Ab). The data was analyzed by SPSS 21. Results: The serum IL-36γ show correlation with the TOP-Ab and FT3 in HT. The IL-36γ was significantly higher in HT as compared to the control group; p<0.001**. The IL-36γ show significant negative correlation with TOP-Ab (<0.001**, r-0.126) and non- significant positive correlation with FT3 (0.321, r= + 0.28) in HT patients. The Tg-Ab was show non- significant correlation with IL-36 γ; (P<=0. 928, r = 0.323). Conclusions: IL-36 γ is diagnostic marker and show negative correlation with TPO-Ab in the patient serum of HT. Il-36 γ had significantly high in the HT patients. IL-36 γ may involve to the progression of pathogenesis and enhance the inflammatory responses. In HT, Tg-Ab was significantly reduced than TPO-Ab but both contribute to the production of thyroid hormones. Keywords: Interleukin, Thyroxin, Thyroid stimulating hormone, Peroxidase.